Exploring Self-Management of Adults Living with HIV on Antiretroviral Therapy in North-West Ethiopia: Qualitative Study - Areri, Habtamu (HIV AIDS (Auckl), 2020)
BACKGROUND: The changing nature of HIV from an acute to chronic illness requires adults living with HIV to self-manage. Self-management enables individuals with HIV to maintain physical health, medication adherence and live with HIV-related conditions. This study aimed to explore self-management experiences of adults living with HIV on antiretroviral therapy in Ethiopia. METHODS: A qualitative descriptive study framed by the Individual and Family Self-Management Theory was carried out to explore the self-management experience of adults living with HIV in Northwest Ethiopia. Eleven semi-structured, in-depth interviews were conducted. The recruitment involved participants who volunteered to be contacted during a preceding quantitative study. The interview data were coded inductively and subject to thematic analysis. RESULTS: The main themes identified, each with a number of sub-themes, related to perceptions and experience of self-management, barriers and facilitators of self-management. Factors influencing self-management behaviour were inter-connected and particularly influenced by spiritual practices, low levels of income and experiences of stigma and discrimination. CONCLUSION: The study highlights barriers to self-management among individuals living with HIV on antiretroviral therapy in a resource-constrained country. Interventions to address modifiable barriers and build on identified facilitators of self-management include working with the broader community to minimise HIV-related stigma and discrimination and engaging with religious leaders to tackle the observed conflict between spiritual practice and effective self-management behaviour.